Ajaran para leluhur : koleksi Perpustakaan Nasional RI. - Perpustakaan Nasional (Indonesia) ([Jakarta] : Perpustakaan Nasional RI, 1994)
Collection of romanized texts of four Malay, one Buginese, one Balinese, and one Kawi manuscripts in the collection of the National Library.
Hikayat seribu masail -- Al-hayatu l-qulub -- Syair kiamat -- Syair nasehat -- Pappaseng -- Singhalangghyala parwa -- Sasana sunu.
Indonesian translations, includes original Balinese, Buginese, and Kawi texts.
Keywords: Social ethics -- Indonesia